The effect of cholesterol on the survival and development of larval mud crab Scylla serrata were examined by feeding larvae with Artemia enriched with different level of cholesterol. Artemia enriched with four stated levels of cholesterol i.e., 0, 5, 10, and 20 ul/l (Chol 0, 5, 10, and 20). All treatments were mixed with DHA70G at 25 ul/l. All the oil was adjusted to 100 ul/l by adding the oleic acid. Survival rate, intermolt period, and carapace width at the fisrt crab stage of mud crab larvae - MUHAMMAD AGUS SUPRAYUDI; TOSHIO TAKEUCHI; KATSUYUKI HAMASAKI (HAYATI Journal of Biosciences, 2012)
The effect of cholesterol on the survival and development of larval mud crab Scylla serrata were examined by feeding larvae with Artemia enriched with different level of cholesterol. Artemia enriched with four stated levels of cholesterol i.e., 0, 5, 10, and 20 ul/l (Chol 0, 5, 10, and 20). All treatments were mixed with DHA70G at 25 ul/l.  All the oil was adjusted to 100 ul/l by adding the oleic acid. Survival rate, intermolt period, and carapace width at the fisrt crab stage of mud crab larvae fed Chol 0, 5, and 10 were higher compared to that of Chol 20 (P < 0.05). We suggest that free sterol contained in Artemia at 1.37% was harmful to the growth performance of mud crab larvae. This study suggests that mud crab larvae required at least 0.61% cholesterol for maintaining good survival and development and therefore no need to enrich Artemia by cholesterol for the practical purpose.